IMPLEMENTASI KONVENSI INTERNASIONAL TENTANG HAK ANAK (Convention on The Rights of The Child ) DI INDONESIA ( Studi kasus : Pelanggaran Terhadap Hak Anak di Provinsi Kepulauan riau 2010-2015) - Raissa Lestari; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In the fulfillment of children’s welfare with the protection approach from various aspects tried have not been satisfactory yet. Admitted that the children’s protection policy and the children’s welfare policy have been accommodated by various interests. Yet, if it is not supported by facifacilities and infrastructuctures, it will not bring a result. In the context of the human rights protection, children’s protection is not only national problem but also international problem. It have been seen in some international documents protecting of children’s problem.The convention of children’s right is one form that children’s protection problem in the world that should be protected and the convention implementationhas prevailed in legislation that had been passed by the KEPRES Number. 36 in 1990 in order to give protection to children’s welfare interests. Then the law number: 39, year 1999 is about Human rights.Key : Human Rights, Convention of children’s Right